Implementation of Social Media Influencers in Building Brand Image at Courtyard by Marriott Bali Nusa Dua Resort - Ningsih, Ni Ketut Manohara Raditya; Winia, I Nyoman; Armoni, Ni Luh Eka; Septevany, Elvira (Universitas Muhammadiyah Tangerang, 2025)
This study aims to determine social media influencers' influence on building Courtyard's brand image by Marriott Bali Nusa Dua Resort. The data collection method used in this study is by conducting observations and distributing questionnaires. The population of this study was Instagram users who follow Instagram social media influencers and the Courtyard by Marriott Bali Nusa Dua Resort, with a sampling technique using purposive sampling with a sample size of 100 respondents. The data analysis technique used in this study is simple linear regression. The results of this study indicate that the implementation of social media influencers has a strong relationship, as evidenced by a simple correlation test with a coefficient of 0.724 and has a positive and significant effect on brand image. The value of the coefficient of determination is 0.524, which means that social media influencers have an influence of 52.4% in improving the brand image at Courtyard by Marriott Bali Nusa Dua Resort, while the remaining 47.6% is influenced by other factors not examined in this study. The indicators of social media influence, namely visibility, credibility, attractiveness, and power, state that each indicator has its role in building brand image. If each indicator is applied optimally, it will positively impact brand image. However, it is better to consider the power criteria that are owned because it can maximize the number of audiences who are influenced and follow the directions of the promotion carried out by social media influencers.